RENE GİRARD’IN ARZU MODELİ BAĞLAMINDA DIŞ GÖÇ ROMANLARINDA ÖZNE-NESNE İLİŞKİSİ - Özdemir, Burak (Ulakbilge sosyal bilimler dergisi, 2019)
The movement of workers migration to Germany, which starded in the 1960s, has been the subject of narratives such as novels, stories and poems, and has become a frequently encountered theme in recent Turkish literatüre. The novels examined in this study are the ones that deal with the first period of labor migration to Germany. These novels focused on the problems of Turkish immigrants with a realistic approach. This structure , which constitutes the internal integrity of the texts, has been constructed in line with the subject-object relationship. The focus of this study is on the common structure of Rene Girard’s "model of desire" and syntactic contexts of international migration novels.